Allegiance and identity in a globalised world / edited by Fiona Jenkins, Mark Nolan and Kim Rubenstein. - Jenkins, Fiona; Nolan, Mark Andrew; Rubenstein, Kim (Connecting international law with public law., 2014)
Interrogating the concepts of allegiance and identity in a globalised world involves renewing our understanding of membership and participation within and beyond the nation-state. Allegiance can be used to define a singular national identity and common connection to a nation-state. In a global context, however, we need more dynamic conceptions to understand the importance of maintaining diversity and building allegiance with others outside borders. Understanding how allegiance and identity are being reconfigured today provides valuable insights into important contemporary debates around citizenship. This book reveals how public and international law understand allegiance and identity. Each involves viewing the nation-state as fundamental to concepts of allegiance and identity, but they also see the world slightly differently. With contributions from philosophers, political scientists and social psychologists, the result is a thorough appraisal of allegiance and identity in a range of socio-legal contexts.